2015
DOI: 10.2196/jmir.4427
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Information Seeking and Drug-Safety Alert Response by Health Care Professionals as New Methods for Surveillance

Abstract: BackgroundPatterns in general consumer online search logs have been used to monitor health conditions and to predict health-related activities, but the multiple contexts within which consumers perform online searches make significant associations difficult to interpret. Physician information-seeking behavior has typically been analyzed through survey-based approaches and literature reviews. Activity logs from health care professionals using online medical information resources are thus a valuable yet relativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 28 publications
0
14
0
1
Order By: Relevance
“…Earlier studies on health information-seeking behavior of Internet users have studied the relationship between search behavior and health concerns of search users. For instance, it has been shown that physician information-seeking behavior, as assessed by the mean page view duration for specific websites, is distinct from general online media activity [ 19 ]. Health anxiety in patients has also been shown to be associated with specific search patterns, such as intense search activity punctuated by periods of calm [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…Earlier studies on health information-seeking behavior of Internet users have studied the relationship between search behavior and health concerns of search users. For instance, it has been shown that physician information-seeking behavior, as assessed by the mean page view duration for specific websites, is distinct from general online media activity [ 19 ]. Health anxiety in patients has also been shown to be associated with specific search patterns, such as intense search activity punctuated by periods of calm [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, more and more physicians use the convenience of the Internet to search drug information [8] and Web-based evidence sources such as UpToDate [9] for providing better medical care to patients.…”
Section: Introductionmentioning
confidence: 99%
“…However, in search engines providing access to a specific type of content or collection ("vertical search engines"), the search functionality is often different, hence, user behavior can be expected to differ. This has been shown, for example, for image archives (Han and Wolfram, 2015;Hollink et al, 2011), a medical knowledge portal (Callahan et al, 2015), a newspaper archive (Gooding, 2016), and in a study of a digital library (Niu and Hemminger, 2015).…”
Section: Introductionmentioning
confidence: 84%